Effectiveness of lifestyle interventions on preventing diabetes in adults at high risk of type 2 diabetes: a systematic review protocol. (March 2019) - Wechkunanukul, Kannikar; Benton, Fiona; May, Nikki
Abstract : Review question: The question of this review is: Is lifestyle intervention effective in preventing type 2 diabetes in adults identified as being at high risk of developing type 2 diabetes? Additional specific review sub-questions are: What are the effects of the intervention elements (e.g. number and length of sessions, components and length of intervention, mode of delivery) on the overall success of intervention? Are there factors (e.g. demographics, clinical and behavioral factors) that influence the effectiveness of interventions? What are the effects of intervention on quality of life?